Dancing to Devotion: The Hindu Aesthetic and Spiritual Significance of Abuang Dance in Tenganan Pegringsingan Bali - Pancane, Iwayan Dikse; Prawita, Ni Ketut Riska Dewi; Mustika, I Ketut; Johnson, Davida (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to explore the cultural and spiritual significance of the Abuang dance within the Usaba Kasa ceremony in Tenganan Pegringsingan, highlighting its role in maintaining cultural identity and spiritual continuity. The study utilised qualitative methods, including participant observation, in-depth interviews, and video documentation, to gather primary data concerning the Abuang dance. Secondary sources were employed to enrich the contextual understanding of the dance’s historical and cultural relevance. This research found that the Abuang dance is not merely a form of cultural expression but also serves as an integral component of the religious and communal life in Tenganan Pegringsingan, encapsulating the Hindu aesthetic values of satyam (truth), sivam (chastity), and sundaram (beauty). The dance fosters cultural resilience and acts as a conduit for spiritual and communal values amidst contemporary challenges. The study contributes to the wider discourse on the preservation of cultural heritage, providing insights into how traditional dances can sustain community values and spiritual life in modern contexts. It further highlights the importance of integrating cultural practices into global discussions on cultural and spiritual sustainability.